"It Was Worse than My Son Passing Away." The Experience of Grief in Recovering Crack Cocaine-Addicted Mothers Who Lose Custody of Their Children. (July 2017) - Janzen, Katherine J.; Melrose, Sherri
Grief could be considered to be the universal experience notwithstanding the cause. For addicted mothers, grief is a constant companion after losing custody of their children often leading them to attempt suicide and engage in self-destructive behaviors. Little is known about the processes and symptoms of grief in these mothers. This hermeneutic study explores the grief of four crack cocaine recovering mothers who lost custody of their children. Thematically, three nonlinear stages were identified that the mothers passed through in an iterative manner: betrayal, soul-ache, and reclamation. Posttraumatic growth was identified as an outcome once the mothers entered recovery. It is imperative that clinicians from all disciplines recognize and respond to the grief that addicted mothers who lose custody of their children experience, through the offering of grief support and grief counseling.